Implementasi Kebijakan dan Proses Pengembangan Koleksi Digital Perpustakaan Perguruan Tinggi Vokasi (Studi Kasus Perpustakaan Politeknik Negeri Malang) - Ach. Nizam Rifqi; Verry Mardiyanto (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2020)
This paper describes the implementation of policies and the process of developing digital collections with research objects in vocational college libraries with cases in the Malang State Polytechnic library. This paper is based on the implementation of policies and development processes as a whole on a digital library collection with a real qualitative approach to the actions of each activity process. The purpose of this research is to describe the diagram results regarding the processes and results of digital collection policies. The results obtained from this research are, the category of implementation of the digital collection development policy of the State Polytechnic Library of Malang which is divided into 4 policies, namely: the development policy for mapping the sub-discipline of collection science, the policy on the structure of the collection development team, the policy on the implementation time period and the policy on the source of the collection digital. The next results regarding the process of developing a digital collection of the Malang State Polytechnic library are divided into 5 processes, namely: community analysis, selection policies, acquisition, weeding and collection evaluation. From the results of the discussion, the Malang State Polytechnic library has a policy for implementing the digital collection development process so that the results of digital collections can be utilized by students and the academic community as a whole